CONCERNING IBN ‘ARABI’S ACCOUNT OF KNOWLEDGE OF GOD (MA‘RIFA) AL-ḤAQQ - Andi Herawati (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2013)
This paper tries to reveal the concept of ma’rifa developed by Ibn al-‘Arabi (d. 1260), especially in his magnum opus, Fuṣūṣ al Hikam, the late work considered to be the synthesis of his doctrine of metaphysics represented through the wisdom of each prophet; their uniqueness of divinely inspired and their epitome of spiritual perception, concerning the knowledge of God. It shows the transformative role of the prophet’s messages involving in the deeper creative process of divine-human dialogue, calling and response, that is repeatedly mentioned in the Qur’an. Ibn ‘Arabi emphasized the importance of perceiving the direct relationship between all of creation and the divine Names and Attributes (al-asmā’ wa-l-sifāt al-ilāhiyyah), between creation as outward manifestation and as inward spiritual awareness (rūh). Everything that exists and is experienced in reality is the manifestation (tajallī) of different divine Names.